Defining Student's Achievement Based on The Understanding of National Education Philosophy and Malaysia's Education Blueprint (2013-2025) - Jude James; Rosy Talin; Soon Singh Bikar Singh (Secholian Publication, 2022)
This study aims to define students' achievement based on the National Education Philosophy and Malaysia's Education Blueprint (2013-2025) and propose a proper definition of students' achievement used for future study. This is done by extracting the meaning of students' achievement from the National Education Philosophy and Malaysia's Education Blueprint (2013-2025) and comparing it to existing studies done in Malaysia. Based on the discussion, a proper theoretical framework will be proposed as a definition for student achievement in Malaysia for future researchers in the field of education. This will provide fundamental knowledge and direction for researchers and practitioners to further contribute to the thin knowledge base concerning Malaysia's education field's future improvement.